TEACHERS’ EMOTIONAL REGULATION AND NON-VIOLENT DISCIPLINE IN SCHOOLS: A QUALITATIVE STUDY WITHIN INDONESIA’S PPKSP POLICY - Ikram Shiddiq; Sabran Sabran; Mowafg Masuwd (STAI Asy-Syukriyyah, 2026)
The implementation of non-violent discipline has become an essential demand in education following the policy on the Prevention and Handling of Violence in Educational Institutions (PPKSP). However, its implementation in classroom settings still faces challenges, particularly related to teachers’ ability to regulate emotions and respond to student misconduct constructively. This study aims to formulate a model of teachers’ emotional regulation and assertive communication in implementing non-violent discipline. This research employed an exploratory qualitative approach, with data collected through open-ended questionnaires distributed via Google Forms to teachers. Data were analyzed using thematic analysis to identify patterns and meanings from teachers’ experiences. The findings reveal that non-violent discipline is implemented through a structured process involving emotional regulation, assertive communication, and educational consequences. Based on these findings, this study proposes a model consisting of three main stages: internal regulation, assertive communication, and educational consequences. This model highlights that teachers’ emotional regulation serves as the foundation for creating firm, humane, and character-oriented discipline in the classroom.